2020
DOI: 10.1108/jamr-01-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Developing a marketing framework for the bottom of the pyramid consumers

Abstract: PurposeThis paper develops a comprehensive marketing framework that firms could use as a foundation for developing a successful business model that ensures sustainability in BOP markets.Design/methodology/approachThe study employs a qualitative research approach based on semi-structured in-depth interviews with founders or senior managers of Indian firms who have been successfully operating in the Indian BOP market. The data is then systematically coded and categorized with the help of software to get better i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Several attempts have been taken to develop the marketing strategies at BOP by effectively structuring the marketing mechanisms (Ghosh et al, 2019(Ghosh et al, , 2020a. Also, various attempts have been taken to synthesize how the co-creation concept can improve the marketing values in the developing economies, but the studies to analyze how cocreation activities may develop the market economy at the BOP level remained unexplored (Kumar et al, 2019a(Kumar et al, , 2019bMathur et al, 2020). Hence, to fill up this gap, it is essential to investigate how different factors such as social media usage at BOP, social influence, development of digital knowledge of the people at BOP might help to co-create values at BOP (Zadeh et al, 2019), especially, when it is observed that a considerable number of people are spending time using the internet at BOP level (Ericsson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been taken to develop the marketing strategies at BOP by effectively structuring the marketing mechanisms (Ghosh et al, 2019(Ghosh et al, , 2020a. Also, various attempts have been taken to synthesize how the co-creation concept can improve the marketing values in the developing economies, but the studies to analyze how cocreation activities may develop the market economy at the BOP level remained unexplored (Kumar et al, 2019a(Kumar et al, , 2019bMathur et al, 2020). Hence, to fill up this gap, it is essential to investigate how different factors such as social media usage at BOP, social influence, development of digital knowledge of the people at BOP might help to co-create values at BOP (Zadeh et al, 2019), especially, when it is observed that a considerable number of people are spending time using the internet at BOP level (Ericsson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we use the 4A framework that consists of awareness , accessibility , affordability , and acceptability (Sheth and Sisodia 2012), to examine the impact of marketing activities on market development (i.e., access to markets and access to people) and value created (i.e., financial value and relationship value). It is well accepted in the literature that the 4A framework is more useful for analyzing emerging market conditions (Anderson and Billou 2007; Dadzie, Amponsah, and Winston 2017); Mathur, Mehta, and Swami (2020); Prahalad 2004; Seth and Sisodia (2012); Sinha and Seth (2018)) compared to other marketing frameworks (e.g., 4Ps, 7Ps of marketing mix). Thus, this research aims to fill important research voids in examining how each of the 4A’s can lead to market development, and value creation in EMs (Prahalad 2012; Sheth and Sisodia 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The content for i-shakti was available in local languages and was developed by NGO's such as, Azim Premji Foundation (Banerjee, 2010). Another kind of organisation sponsoring social marketing can be a for-profit organisation focused on creating value for the people at the bottom of the pyramid (BOP) (Mathur et al ., 2020). The core characteristics of the BOP business model are alleviating poverty by treating the BOP as customers in the value chain and creating mutual value while making profits (Martinez and Carbonell, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%